The Influence Of Accessibility, Amenity, And Social Media On Piugus Resort Tourism Selection Decisions In Anambas With Tourism Attraction As An Intervening Variable - Zaili Zaili; Chablullah Wibisono; M. Gita Indrawan (Brilliant International Journal Of Management And Tourism, 2023)
Tourism is a benchmark for the attractiveness of an area's progress in attracting migrants to visit. It aims to improve the economic welfare of the surrounding community. Anambas is an archipelago that has very exotic and beautiful water tourism, which is rarely found in other parts of Indonesia. Piugus Resort is one of the leading resorts in Anambas, visited by tourists. The purpose of this study was to determine and analyze the direct and indirect effects of accessibility, amenities, and social media variables on the decision to choose Piuggus Resort or tourist attractions. The research approach uses quantitative descriptive methods. The research method uses Path Analysis. The results of the study Accessibility has a positive and significant effect on tourist attraction. Amenity has a positive and significant effect on tourist attraction. Social media has a positive and significant effect on tourist attraction. Accessibility has a positive and significant effect on the decision to choose Piugus Resort. Amenity has a positive and significant effect on the decision to choose Piugus Resort. Social media has a positive and significant effect on the decision to choose Piugus Resort. Tourism attraction has a positive and significant effect on the decision to choose Piugus Resort. Accessibility indirectly has a significant effect on the decision to choose Piugus Resort through tourist attractions. Amenity indirectly has a significant effect on the decision to choose Piugus Resort through tourist attractions. Social media indirectly has a significant effect on the decision to choose Piugus Resort through tourist attraction.